ChemInform Abstract: Catalyst‐Controlled C—O versus C—N Allylic Functionalization of Terminal Olefins. Issue 6 (11th February 2014) - Strambeanu, Iulia I.; White, M. Christina
Abstract Depending on the reaction conditions and especially the reaction time, the substrates can be converted to either aminooxazolines or imidazolidinones (with the respective other being a side‐product in small amounts).